Morphological and molecular based identification of pectinase producing Bacillus licheniformis from rotten vegetable - Haneef Ur Rehman; Nadir Naveed Siddique; Afsheen Aman; Muhammad Asif Nawaz; Abdul Hameed Baloch; Shah Ali Ul Qader (Journal of Genetic Engineering and Biotechnology, 2015)
Pectinase catalyzed the degradation of pectin substances and has been used in various biotechnological industries. In the current study, 23 bacterial strains were isolated from rotten vegetables, soil and air. The isolated bacterial strains were qualitatively screened for pectinase production on pectin agar medium and only three strains HR 4, HR 21 and HR 23 were observed to produce extracellular pectinase. These strains were further screened quantitatively for pectinase production through submerged fermentation technology in pectin containing fermentation medium. Strain HR 4 from rotten brinjal (Solanum melongena) was found to produce higher pectinase as compared to others. The maximum pectinase producing bacterial strain was identified as Bacillus licheniformis on the basis of morphological, physiological and biochemical characteristics. For further confirmation of identification, 16S rDNA sequence analysis was performed. The 16S rDNA sequences were aligned and the phylogenetic tree was constructed. The phylogenetic tree confirmed that the strain was belonging to B. licheniformis. The 16S rDNA sequences of this new strain were submitted to GenBank and designated as B. licheniformis KIBGE-IB21 with the GenBank accession number JQ 411812. The newly isolated pectinase producing B. licheniformis used apple pectin as carbon and yeast extract as nitrogen source for maximum pectinase production.